Modifications Induced by Rootstocks on Yield, Vigor and Nutritional Status on Vitis vinifera Cv Syrah under Hyper-Arid Conditions in Northern Chile - Nicolás Verdugo-Vásquez; Gastón Gutiérrez-Gamboa; Irina Díaz-Gálvez; Antonio Ibacache; Andrés Zurita-Silva (Agronomy, 2021)
Hyper-arid regions are characterized by extreme conditions for growing and lack of water (<100 mm annual rainfall average), where desertification renders human activities almost impossible. In addition to the use of irrigation, different viticultural strategies should be taken into account to face the adverse effects of these conditions in which rootstocks may play a crucial role. The research aim was to evaluate the effects of the rootstock on yield, vigor, and petiole nutrient content in Syrah grapevines growing under hyper-arid conditions during five seasons and compare them to ungrafted ones. St. George induced lower yield than 1103 Paulsen. Salt Creek induced higher plant growth vigor and Cu petiole content than ungrafted vines in Syrah, which was correlated to P petiole content. However, Salt Creek and St. George rootstocks induced an excess of vigor in Syrah according to Ravaz Index. Rootstocks with V. berlandieri genetic background should be used in Syrah growing under hyper-arid conditions to maintain adequate levels of plant vigor and to avoid deficiencies or toxicity of macro and micronutrients.